2022
DOI: 10.3390/cancers14020292
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Operative Electron Radiation Therapy (IOERT) Anticipated Boost in Breast Cancer Treatment: An Italian Multicenter Experience

Abstract: In breast cancer, the use of a boost to the tumor bed can improve local control. The aim of this research is to evaluate the safety and efficacy of the boost with intra-operative electron radiotherapy (IOERT) in patients with early-stage breast cancer undergoing conservative surgery and postoperative whole breast irradiation (WBI). The present retrospective multicenter large data were collected between January 2011 and March 2018 in 8 Italian Radiation Oncology Departments. Acute and late toxicity, objective (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Conventionally fractionated WBI (50 Gy in 5 weeks) combined with IORT photon boost was shown to be a standard alternative to other boost techniques [ 29 ]. Moderate hypofractionation WBI (40.05 Gy in 3 weeks) combined with an IORT boost has been confirmed to be safe and feasible using both electrons [ 30 , 31 , 32 , 33 ] and photons [ 15 , 16 , 34 , 35 ]. Our pioneering experience has shown that the combination of immediate IORT plus moderate HWBI is accompanied by favorable results in relation to chronic toxicity and aesthetic results, both in patients with early and locally advanced disease [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally fractionated WBI (50 Gy in 5 weeks) combined with IORT photon boost was shown to be a standard alternative to other boost techniques [ 29 ]. Moderate hypofractionation WBI (40.05 Gy in 3 weeks) combined with an IORT boost has been confirmed to be safe and feasible using both electrons [ 30 , 31 , 32 , 33 ] and photons [ 15 , 16 , 34 , 35 ]. Our pioneering experience has shown that the combination of immediate IORT plus moderate HWBI is accompanied by favorable results in relation to chronic toxicity and aesthetic results, both in patients with early and locally advanced disease [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, IORT boost is an excellent treatment when using moderate hypofractionation radiotherapy and is therefore worthy of being combined with an ultrafractionation WBI protocol that produces similar toxicity figures to the moderate hypofractionation protocols [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the safety and efficacy of administering the boost during WBI using modern techniques such as Intensity Modulated RT (IMRT) or Volumetric Modulated Arc RT (VMAT) with alternative splitting schemes [ 38 , 39 , 40 ]. Moreover, boosts should be administrated as intra-operative RT, reporting similar results in terms of efficacy and toxicity compared to external beam techniques [ 41 , 42 , 43 , 44 , 45 ]. The results of the pilot Breast IRRADIATA showed that the boost was administrated in only 64% of cases, generally as sequential with a 3D conformal RT technique.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between WBI schedules were not reported. This series also obtained optimal local control and survival [ 44 ]. More interestingly in a recent publication of an HIOB prospective trial, all patients included received electron IORT of 11.1 Gy followed by hypofractionated WBI of 40.5 Gy (15 fractions).…”
Section: Bed Boost With Iortmentioning
confidence: 99%